Reviewing fair subject selection considerations for the unique case of post sequelae COVID-19 translational studies. Issue 1 (7th July 2022) - Smith, E.M.; Anderson, E.E.; Deer, R.; Prochaska, J.; Bohn, K.; Croisant, S.
Abstract: Fair inclusion of research subjects is necessary to ensure that post-acute sequelae COVID-19 (PASC) research results benefit all members of society. Scientists should conduct research on a broad sample of individuals who represent clinically relevant factors influencing a disease. Without demographic diversity and sociological and environmental variability, research outputs are less likely to apply to different populations and would thus increase health disparities. The goal of this narrative literature review and ethical analysis is to apply fair selection criteria to PASC research studies. We briefly highlight the importance of fair subject selection in translational research and then identify features of PASC, as well as PASC research, that hinder fair inclusion of research participants. We will demonstrate that determining an adequate and representative sample is not simply a matter of ensuring greater diversity; rather, fairness requires a broader evaluation of risks, burdens, and benefits specific to underrepresented populations. We provide recommendations to ensure fair subject selection in PASC research and promote translation toward positive health outcomes for all individuals, including the most vulnerable.